Hardness and quality of abalone (Haliotis discus hannai diversicolor diversicolor) muscle as suitably softened for seniors. Issue 1 (1st January 2021) - Lin, Hong-Ting Victor; Wu, Hao-Xuan; Sung, Wen-Chieh
ABSTRACT: This study aims to evaluate the effects of different softening methods on the texture and quality of abalones ( Haliotis discus hannai × Diversicolor diversicolor ). We monitored the hardness, meat weight, pH, size, and appearance from the sterilized abalones pre-treated with alkaline soaking and enzymatic injection/soaking, with either vacuum orbital shaking or ultrasonic processing. The hardness of the abalones was reduced by alkaline and enzymatic treatments, and combined vacuum orbital shaking or ultrasound treatment and this could increase their tendering effects. The softest abalone was obtained by bromelain comparing to papain injection, and the TVBN measurements indicated that the abalones remained in a fresh state under all treatments. Both enzymatic treatments showed a dose-dependent effects on hardness and pH of sterilized abalones. The abalones pre-treated with injecting enzyme exhibited significant softening effect than soaking method. Histological observation indicated that severe fracturing and non-uniform large spaces between muscle fibers were observed in the abalones injected with bromelain, and the abalones subjected to NaHCO3 soaking showed distorted muscle fibers and small uniform spaces. SDS-PAGE further indicated the decrease of paramyosin in the abalones injected with bromelain. Sensory evaluation using senior panelists without chewing difficulties indicated that NaHCO3 soaking before sterilization exhibited the highest overall acceptability, possibly because this method could slightly soften abalone foot while retaining its palatability. This study should benefit the food industry in terms of developing and processing food for senior citizens.